The Effect of Community Participation, Government Policy, and Sharia Financial Education on Sharia Economic Development in West Java - M. Novan Fithrianto; Mufid Andrianata; Judi Suharsono (Westscience Press, 2024)
This study investigates the effect of community participation, government policy, and Islamic financial education on the development of Sharia economics in West Java. Utilizing a quantitative approach, data were collected from 160 respondents using a Likert scale ranging from 1 to 5. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings indicate that all three hypotheses are positive and significant. Community participation, government policy, and Islamic financial education each have a substantial impact on fostering the growth of Sharia economics in the region. Specifically, Islamic financial education demonstrated the most substantial effect, followed by government policy and community participation. These results underscore the critical roles of community engagement, supportive governmental frameworks, and educational initiatives in advancing the Islamic economic system in West Java. The study provides valuable insights for policymakers, educators, and community leaders aiming to enhance the development of Sharia economics through targeted strategies and programs.